Seed pre-treatment in rice reduces damage, enhances carbohydrate mobilization and improves emergence and seedling establishment under flooded conditions - Ella, Evangelina S.; Dionisio-Sese, Maribel L.; Ismail, Abdelbagi M. (Oxford University Press, 2011)
Early flooding helps control weeds but reduces seedling establishment in direct-seeded rice (Oryza sativa). When combined with appropriate management practices, the use of genotypes that better tolerate flooding during emergence can enhance crop establishment in flood-prone areas. Management options include seed pre-treatment and we tested the influence of pre-soaking for 24 h prior to sowing or of priming (soaking for 24 or 48 h followed by drying). The effects on seedling establishment after 21-day flooding of pre-soaking seeds for 24 h before sowing and/or of priming seeds were examined together with physiological responses connected with reactive oxygen scavenging. Seeds of four lines with contrasting abilities to tolerate flooding at the germination stage were compared. Seeds were primed using KCl solutions (48 h) or water (24 h) and pre-soaked using water. Lipid peroxidation and activities of reactive oxygen-scavenging enzymes were measured in seeds before sowing. Carbohydrate mobilization in germinating seeds and seedling growth were also monitored at intervals. Seed pre-treatment by pre-soaking or by priming increased survival of flooding and accelerated and improved seedling establishment, especially in tolerant genotypes. Primed seeds had less lipid peroxidation and higher superoxide dismutase (SOD) and catalase (CAT) activities than non-primed seeds. Amylase activities and starch breakdown were also hastened in primed seeds. Survival after flooding was positively correlated with amylase activity but negatively correlated with the extent of lipid peroxidation. Pre-soaking and priming improved seedling establishment in flooded soil, enhanced the capacity to scavenge reactive oxygen species in seeds by increasing SOD and CAT activities, and hastened carbohydrate mobilization. Tolerant genotypes responded better to these treatments, emphasizing the effectiveness of combining genetic tolerance with appropriate seed pre-treatment to improve seedling establishment of rice sown in flooded soils.